Sofrimento psíquico entre estudantes de Medicina da UFMG: uma contribuição da Assessoria de Escuta Acadêmica - Maria das Graças Santos Ribeiro (2014)
Making room for the acceptance and listening to psychological distress in Medical students through the academic and administrative systems highlights the importance of considering the uniqueness of these students for health care and for the course. The Office of Academic Listening of the Center of Graduate Studies of the UFMG School of Medicine enables this project which has made possible to get to know and mediate, often prematurely, situations of suffering. Doubts about career choice, academic complaints and discontentment, cancellation of enrolment, conscious and unconscious reasons for attitudes and behaviors, non-attendance of classes, failure, competition, abusive use of alcohol and other drugs, thoughts of suicide, violence and segregation and many others are emerging as symptoms, subjective responses of a restlessness experienced by students which could become known by the opening of a space for this listening. The aim was to investigate what is hidden between academic / administrative requests that is due to emotional distress and mental suffering. This is a retrospective cross-sectional study with qualitative and quantitative analysis of appointment records (collected in order to monitor the students) and requests to cancel enrollment by students from 1st. to 12th. semesters of the Medicine graduate program for the period of six years. The qualitative research used content analysis through categorizations, in order to discuss the data. The sampling, for the appointment records, was collected deliberately by saturation criteria. For cancelations, all records of the six years surveyed were used. The statistical analysis was performed using descriptive statistics, percentage and cross-frequencies, and percentages. This analysis identified that 59.6% of the dropouts have their justification based on mental suffering. Among all cancelation requests, 55.3% happened in the Basic Cycle of the course, 35.5% in the Ambulatory Cycle and only 9.2% in Internship Cycle, which points to the importance of paying greater attention to the students at the beginning of the course. In the three cycles most requests were motivated by psychological distress: 62.8%; 52% and 69.2%, respectively. Some situations of emotional suffering - 15.2% of the students who had their appointment records analyzed - are related to issues identified as prior to attending medical school. The offer of a listening space for students was presented as a possibility for making decisions regarding the search for treatment and about the career choice, besides offering support in times of psychological distress, with the inclusion of the family and teachers in the ongoing situation. This space proved to be critical for the care of the student, promoting better conditions for life and academic quality, and can help the colleges to reflect and make referrals regarding difficulties in the relations of students to the classes and teachers. Some characteristics of the course are also factors that could reveal, start or make these conditions worse. Thus, the painful situations are multifactorial and carry within them the delicacy of subjectivity, unique to each student.